Caracterización de la Ganancia del SiPM MPPC S13360-6025CS (2022)
The Silicon photomultipliers (SiPM) are widely used devices and have direct application in various scientific fields. For example, in the detection of fluorescence for biomedical purposes such as nuclear medicine, gene expression (key to phenotyping), study of biochemical cycles (e.g. carbon cycle). [1], [2] In the present work, the SiPMs are used as photon detectors; the detection can be affected by the temperature variation; therefore, in the Antonio Nariño University a research line was created focused on determining the changes of the characteristics in the detectors, For this, we designed an additional box to the characterization plant that is composed by the power supply, the board for temperature control, cooling system, an Arduino Mega 2560 board and 8 output ports for connecting the cells and sensors, whose its function is to control the temperature of the peltier cells, ensuring a stable behaviour